T2-Weighted MR Imaging Early after Chemoradiotherapy to Evaluate Treatment Response in Head and Neck Squamous Cell Carcinoma - King, A.D.; Keung, C.K.; Yu, K.-H.; Mo, F.K.F.; Bhatia, K.S.; Yeung, D.K.W.; Tse, G.M.K.; Vlantis, A.C.; Ahuja, A.T. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: T2-weighted MRI shows potential in early posttreatment assessment of the primary tumor. Residual masses composed entirely of low T2-signal scar tissue suggest local control and those ≥1 cm of similar signal to untreated tumor suggest local failure. The purpose of this study was to investigate the diagnostic accuracy of T2-weighted MR imaging early after chemoradiotherapy for identifying primary tumor treatment failure in squamous cell carcinoma of the head and neck. MATERIALS AND METHODS: At 6 weeks after treatment, T2-weighted MR images of 37 primary tumors in 37 patients were assessed. Residual masses were divided into 3 patterns: pattern 1 = scar tissue only (flat-edged/retracted mass of low T2 signal intensity); pattern 2 = mass without features described in pattern 1 or 3; and pattern 3 = any pattern that included an expansile mass ≥1 cm of intermediate T2 signal intensity (similar grade of signal intensity to the untreated tumor). T2 patterns were analyzed for local outcome (Fisher exact test) and time to local failure (univariate and multivariate analysis of T2 pattern, age, T stage, and tumor size by use of the Cox regression model). RESULTS: Residual masses after treatment were present in 34 (92%) of 37 patients. Local failures occurred in residual masses with pattern 1 in 0 (0%) of 14 patients; pattern 2 in 6 (55%) of 11 patients; and pattern 3 in 9 (100%) of 9 patients. Significant associations were found between local control and pattern 1 (P = <.0001; sensitivity, 74%; specificity, 100%; PPV, 100%; NPV, 75%; accuracy, 85%), and between local failure and pattern 3 (P = <.0001; sensitivity, 60%; specificity, 100%; PPV, 100%; NPV, 76%; accuracy, 82%). Pattern 2 showed no significant associations with local outcome. Univariate analysis of time to local failure showed that the T2 pattern was significant (P < .0001) and remained significant on multivariate analysis. CONCLUSIONS: T2-weighted MR imaging is a potential tool for early posttreatment assessment of primary HNSCC treatment response. Awareness of correlation of the T2 pattern of any residual mass with treatment outcome at the primary site may contribute to patient treatment. CIconfidence intervalCRTchemoradiotherapyHNSCChead and neck squamous cell carcinomaNPVnegative predictive valuePPVpositive predictive value